Le documentaire libanais contemporain à travers l’étude de trois films sur l’identité, la nation et la transmission - Michel Tabet (Université de Provence, 2013)
This article focuses on the development of the Lebanese documentary film market through an analysis of three movies produced between 2009 and 2010. It shows how the renewal of Lebanese filmmaking benefits from the convergence of two factors: the increase in Arab funding, and the emergence of a new generation of filmmakers who, unlike the immediate post-war generation, focuses on the functioning of society rather than on the memory of the conflict.